Post – Harmony Sangposangan As Dynamic Existence of Madurese People In Digital era - Hidayatullah, Panakajaya (Resital: Jurnal Seni Pertunjukan, 2020)
Post – Harmony Sangposangan As Dynamic Existence of Madurese People. In Digital era This paper is a result of anthropology research by using cultural studies perspectives. This article, comprehensively, discuss; 1) musical relation between Western and traditional music in sangposangan; 2) a kind of ‘post-harmony’ sangposangan by using musicology analysis through musical text of Angling Madura song. The result of study shows an encounter between western and Madurese traditional music in sangposangan music which can produce a new musical entity (harmony of other).  Post-harmony sangposangan is manifested in dynamic composition which are; 1) dangdut composition in EDM syle, and 2) contrast change from dangdut koplo to pure dangdut. Post-harmony can be read as intuition, emotion, sense and instinct which can drive creative process of sangposangan music. It does not come from rigid notation system but it is constructed from rhythm of Madurese people’s life.ABSTRAKTulisan ini merupakan hasil penelitian antropologi musik dengan menggunakan perspektif kajian budaya. Secara komprehensif artikel ini menelaah tentang 1) relasi musikal antara musik Barat dan tradisional dalam musik sangposangan; 2) menelaah tentang bentuk ‘post-harmoni’ sangposangan melalui analisis musikologis dari teks musikal gending Angling Madura. Hasil kajian menunjukkan bahwa pertemuan musikal antara musik Barat dan tradisional Madura dalam musik sangposangan mampu menghasilkan sebuah entitas musikal yang baru (‘harmoni yang lain’). Post-harmoni sangposangan diwujudkan dalam dinamika garap yang dinamis yaitu 1) garap dangdut ala EDM, dan 2) perubahan kontras dari dangdut koplo ke dangdut piur. Post-harmoni dapat dibaca sebagai sebuah naluri, emosi, sense dan insting yang menjadi penggerak dari proses kreatif musik sangposangan. Ia tidak berangkat dari sistem notasi yang kaku, tetapi dibangun dari ritme kehidupan masyarakat Madura.Kata kunci: Sangposangan; Post – Harmony; Madura, Musik